ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DI MADRASAH ALIYAH DARUN NAJAH: STUDI KASUS KESELARASAN PENDIDIKAN IPS (EKONOMI) DENGAN-NILAI NILAI AGAMA - Fadli, Muhammad; Kurniawan, Moh Usman; Wijaya, Shendy Andrie (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
The Merdeka Curriculum was introduced as an educational reform effort to provide teachers with the flexibility to design contextual and relevant learning, including the integration of religious values into Social Studies subjects, particularly Economics. This study aims to analyze the implementation of the Merdeka Curriculum at Madrasah Aliyah Darun Najah, focusing on the alignment between economic education and Islamic values. This qualitative research adopts a case study approach. Data were collected through in-depth interviews and participatory observations involving the principal, vice principal of curriculum affairs, and social studies teachers. The findings reveal that the implementation of the Merdeka Curriculum at this madrasah has not yet been optimal due to limited teacher understanding, lack of training, and the low academic qualifications of some educators. The learning process remains dominated by one-way lecture methods, which hinder teacher-student interaction and student engagement, and has yet to fully integrate Islamic values into economic education. Therefore, continuous training is needed, not only focusing on the technical aspects of the curriculum but also on pedagogical competence to combine economic education with Islamic principles. Strategies such as role modeling, habituation, and moral guidance are recommended to support the internalization of religious values in the learning process. ABSTRAKKurikulum Merdeka hadir sebagai upaya pendidikan dengan memberikan kebebasan kepada guru dalam merancang pembelajaran yang kontekstual dan relevan, termasuk integrasi nilai-nilai agama dalam mata pelajaran Ilmu Pengetahuan Sosial (IPS), khususnya Ekonomi. Penelitian ini bertujuan untuk menganalisis implementasi Kurikulum Merdeka di Madrasah Aliyah Darun Najah, dengan fokus pada keselarasan antara pendidikan ekonomi dan nilai-nilai agama. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui wawancara mendalam dan observasi partisipatif terhadap kepala madrasah, waka kurikulum, dan guru IPS. Hasil penelitian menunjukkan bahwa implementasi Kurikulum Merdeka di madrasah ini belum berjalan optimal karena keterbatasan pemahaman guru, kurangnya pelatihan, dan rendahnya kualifikasi akademik beberapa pengajar. Pembelajaran masih didominasi metode ceramah satu arah, yang menghambat interaksi dan keaktifan siswa serta belum sepenuhnya mengintegrasikan nilai-nilai keislaman dalam materi ekonomi. Untuk itu, diperlukan pelatihan berkelanjutan yang tidak hanya menekankan aspek teknis kurikulum, tetapi juga kemampuan pedagogis dalam menyatukan pendidikan ekonomi dengan prinsip-prinsip ajaran Islam. Strategi seperti keteladanan, pembiasaan, dan pemberian nasihat direkomendasikan untuk mendukung internalisasi nilai-nilai agama dalam proses pembelajaran.